Assessment and reduction of wind buffeting in an open cabriolet. (4th August 2014) - Barnard, R.H.; Monaghan, P.
This paper describes an investigation into interior comfort levels related to draughtiness and wind buffet in the open cabriolet Aston Martin Virage Volante. The study involved initial wind–tunnel model tests, subsequently followed by track tests using a development prototype. Experimentation included internal air velocity and noise measurements and flow visualisation. Good correlation was found between wind–tunnel and full scale measurements, and between measured gustiness and subjective comfort. As a result of the work, some general design conclusions are drawn concerning the control of interior comfort in open cars, and integration of draught–reducing measures into their design.